RELATIONSHIP BETWEEN PHYSICAL ACTIVITIES OF GIRLS AND THEIR PARENTS WITH GIRLS` ATTITUDES PHYSI CAL ACTIVITY - Nebojša Čokorilo; Milena Mikalački (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2007)
The re se arch was con duc ted on the sam ple of 222 pa rents of ele men tary school - girls, aged 6-7 years from No vi Sad, Som bor, Srem ska Mi tro vi ca, Bač ka Pa lan ka and Zre nja nin. Physi cal ac ti vi ti es of ma le chil dren and the ir pa rents we re al so eva lu a ted by the ir pa rents. That is the ti me when chil dren can con sti tu te ha bits for physi cal exer ci ses. Pas si ve at ti tu de of fe ma le chil dren to wards physi cal exer ci ses are the con se qu en ces of the sa me at ti tu des sha red by pa rents. Wit hin re se arch it is fo und out that the re is a hu ge im por tan ce of pa rents' par ti ci pa tion in chil dren's ac ti vi ti es. That in clu des how much chil dren are physi cal ac ti ve per we ek.